Testi screditati, testi accantonati. Per una rilettura delle saghe degli islandesi ‘post-classiche’ o ‘recenziori’ - Ceolin, Martina (Annali di Ca’ Foscari: Serie Occidentale)
Medieval Icelandic sagas include the so-called ‘post-classical’ or ‘late’ Íslendingasögur (Sagas of Icelanders), a group of fourteenth-century texts that are compelling and innovative, as they challenge narrative conventions, especially from the point of view of genre. However, modern and contemporary critics have often judged them negatively, for example as extravagant or poorly crafted – if they have not ignored them altogether. Taking as an example Finnboga saga ramma (Saga of Finnbogi the Strong), this contribution aims to redress such views and demonstrate how these texts are, instead, the fruit of careful and innovative work by their authors, which deserves to be appreciated and, primarily, to be truly considered by scholars.